2018
DOI: 10.1016/j.redox.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heme oxygenase-1 accelerates mesodermal gene expressions during embryoid body development from mouse embryonic stem cells

Abstract: Heme oxygenase (HO)-1 is an inducible stress response protein and well known to protect cells and tissues against injury. Despite its important function in cytoprotection against physiological stress, the role of HO-1 in embryonic stem cell (ESC) differentiation remains largely unknown. We showed previously that induced pluripotent stem (iPS) cells that lack HO-1 are more sensitive to oxidant stress-induced cell death and more prone to lose pluripotent markers upon LIF withdrawal. To elucidate the role of HO-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Based on the evidence that HO-1 is involved in stem cells differentiation [ 37 , 58 , 59 , 60 ], we analyzed the HO-1 expression in ES cells during this process. First, we exploited ChIP Atlas data-mining platform [ 61 ] to investigate histone modifications and the binding of multiple transcriptional regulators to Hmox1 locus in undifferentiated ES cells and in ES cells subjected to differentiation protocols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the evidence that HO-1 is involved in stem cells differentiation [ 37 , 58 , 59 , 60 ], we analyzed the HO-1 expression in ES cells during this process. First, we exploited ChIP Atlas data-mining platform [ 61 ] to investigate histone modifications and the binding of multiple transcriptional regulators to Hmox1 locus in undifferentiated ES cells and in ES cells subjected to differentiation protocols.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, during ES cells differentiation both HO-1 [ 37 , 58 , 60 , 82 , 83 , 84 ] and p53 [ 24 , 76 , 82 , 85 ] play a relevant role. Using the Chip Atlas platform, we found that in undifferentiated ES cells Hmox1 is associated with negative transcriptional regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, enhanced HO-1 activity inhibits the differentiation of murine muscle precursors [61]. On the other hand, ES cells that do not express HO-1 show higher levels of mesodermal and smooth muscle cell markers during embryoid-body differentiation, suggesting that HO-1 could be regulating the expression of specific genes [22]. Moreover, HO-1 activity contributes to the differentiation and maturation of ES cells into cardiomyocytes [23] and HO-1 knockout PS cells show impaired differentiation toward cardiac lineage [24].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that HO‐1 influences cell differentiation both positively and negatively, depending on the cell type [21]. Particularly, HO‐1 has been reported to upregulate a mesodermal gene expression profile during ES cell differentiation through embryoid‐body formation [22] and was also found to be involved in differentiation of ES cells into functional cardiac cells [23]. In line with these observations, it has been reported that knockout PS cells for Hmox1 displayed attenuated spontaneous cardiac differentiation.…”
mentioning
confidence: 99%
“…HO-1/CO has been shown to downregulate the pluripotency markers Sox2 and Oct4 and may enhance mitochondrial biogenesis and promote ESC differentiation and maturation into functional cardiomyocytes . In a three-dimensional embryoid body (EB) differentiation model, Lai et al used mouse HO-1 knockout ESC lines from HO-1 knockout blastocysts to elucidate the role of HO-1 in ESC differentiation . They showed that the absence of HO-1 led to increased expression of the master mesodermal regulator brachyury and the endodermal marker GATA6.…”
Section: Carbon Monoxidementioning
confidence: 99%